2007
DOI: 10.1038/sj.eye.6703005
|View full text |Cite
|
Sign up to set email alerts
|

Pterygium in an aged Mongolian population: a population-based study in China

Abstract: Aims To determine the prevalence and identify associated risk factors for pterygium in an elderly Mongolian population at high altitude in Henan County, China. Methods A population-based survey was conducted from June 2006 to September 2006. A stratified, clustered, random sampling procedure was used to select 2486 Mongolian people aged 40 years and older. Pterygium was diagnosed and graded clinically as grade 1 (transparent), 2 (intermediate), and 3 (opaque). Risk factors associated with pterygium were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 28 publications
6
27
2
1
Order By: Relevance
“…These results are similar to those by other studies, and most of them confirm that there is a correlation between pterygium and age. [4][5][6][11][12][13][15][16][17] In this study, we found that a VA worse than 20/40 in the better eye is five times more likely among people with pterygium, and although this factor has been assessed in a limited number of studies, they support our findings. This can be due to a change in the convexity of the cornea and development of astigmatism.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These results are similar to those by other studies, and most of them confirm that there is a correlation between pterygium and age. [4][5][6][11][12][13][15][16][17] In this study, we found that a VA worse than 20/40 in the better eye is five times more likely among people with pterygium, and although this factor has been assessed in a limited number of studies, they support our findings. This can be due to a change in the convexity of the cornea and development of astigmatism.…”
Section: Discussionsupporting
confidence: 82%
“…4,6,12,16 There are also reports indicating higher prevalence rates among women, 5,13 and yet some studies found no correlation between pterygium and gender (Table 4). 11,15,17,18 On the basis of the results of this study, the prevalence of pterygium significantly increases with age in both genders. These results are similar to those by other studies, and most of them confirm that there is a correlation between pterygium and age.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…29 Lu J et al had found a positive association between pterygium and dry eye symptoms. 25 Anguria P et al had found no association between unstable tear film (dry eye) and pterygium. 26 Moreno JC et al found that Schirmer's test and TBUT value were significantly reduced in the eyes with pterygium and significant clinical correlation exists between pterygium and dry eye.…”
Section: Clinical Correlation Of Dry Eye and Pterygiummentioning
confidence: 99%